2019
DOI: 10.3390/dj7010018
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Phosphate Metabolism, Periodontal Disease, and Cancer: Possible Global Health Implications

Abstract: An association between periodontal disease and cancer has been established in recent studies, but no common etiology has been identified in the hopes of reducing the global burden of these non-communicable diseases. This perspective article hypothesizes that the determinant mediating the association of periodontal disease with cancer is dysregulated phosphate metabolism. Phosphate, an essential dietary micronutrient, is dysregulated in chronic kidney disease, and both cancer and periodontal disease are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Some studies show similar data for patients with periodontitis and patients without periodontal involvement [47,48], or minimal differences between the levels found in periodontal healthy sites and those with periodontitis [49,50]. Other studies point out considerable increase of crevicular TNF-α in periodontitis [51][52][53], supporting the fact that TNF-α concentration variations can be used to predict the progression of periodontal condition.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies show similar data for patients with periodontitis and patients without periodontal involvement [47,48], or minimal differences between the levels found in periodontal healthy sites and those with periodontitis [49,50]. Other studies point out considerable increase of crevicular TNF-α in periodontitis [51][52][53], supporting the fact that TNF-α concentration variations can be used to predict the progression of periodontal condition.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have reported that periodontitis is closely related to chronic kidney disease 40–43 . Dysregulated Phosphate Metabolism was closed with Periodontal Disease 44 . The urinary protein consists of both NAPs and albumin.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to CKD-MBD, hyperphosphatemia increases phosphate levels in saliva, which is associated with a higher risk of inflammation of the periodontium. Furthermore, higher levels of phosphorus itself are linked to systemic inflammation [71]. This will enhance the association of periodontal disease and CKD.…”
Section: Periodontal Disease and Chronic Kidney Diseasementioning
confidence: 99%